Performance of the Traffic Dikyasa Unit in Preventing Violations of Not Wearing Helmets at the Indramayu Police Station - Lega Ikhwan Herbayu (Indonesian Journal of Police Studies, 2021)
The large number of motorized vehicles in Indonesia requires the Indonesian National Police to be able to create security, safety, order and smooth driving. Considering that there are many traffic accidents in Indramayu Regency, it is an interest to explore public awareness of traffic regulations through violation data. It was found that the number of violations of not wearing a helmet was very high. The purpose of this study is to describe the performance of the Dikyasa Unit in preventing traffic violations without wearing a helmet. The Dikyasa Unit is a unit that plays an important role in prevention in accordance with Law No. 22 of 2009 concerning LLAJ. As well as the types of activities of the Dikyasa Unit in carrying out its duties, namely the provision of Community Education (Dikmas) as regulated in the Juklak/05/V/2003. As an analytical tool to discuss this research, Robbins Performance Theory, Communication Theory and Deming Cycle are used. The approach used in this research is a qualitative approach. Data collection was carried out through interview, observation and document review techniques. Meanwhile, data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of the study found that the performance of the Indramayu Police Dikyasa unit still needed to be improved in terms of the quantity of work and the effectiveness of technology. There are still many people in Indramayu who are not aware of the importance of maintaining safety when driving. No daily activity plan found. In conclusion, the performance of the Indramayu Police Traffic Dikyasa unit is not yet optimal, it is necessary to improve performance to prevent violations.